Acute pancreatitis as a presenting feature of Henoch-Schönlein purpura - Dinler, Gönül; Bek, Kenan; Açikgöz, Yonca; Kalayci, Ayhan Gazi (The Turkish Journal of Pediatrics, 2010)
Henoch-Schönlein purpura (HSP) is the most common small vessel vasculitis of childhood. It is characterized by nonthrombocytopenic palpable purpura, abdominal pain, arthritis, and glomerulonephritis. Although HSP is typically known to be self-limited, serious complications can occur. Acute pancreatitis rarely presents as a complication of HSP. It is even rarer as an initial presenting feature of HSP, before the occurrence of characteristic palpable purpura. Herein, we report a 12-year-old girl with HSP who atypically presented with acute pancreatitis.